ANALISIS RESEPSI PEMILIH PEMULA JAWA TIMUR TERHADAP PERSONAL BRANDING GANJAR PRANOWO DI INSTAGRAM - Phazha, Aurel Rhafli; Tsuroyya, Tsuroyya (Universitas Negeri Surabaya, 2024)
This research aims to analyze the reception of first-time voters towards Ganjar Pranowo's personal branding on Instagram, based on the political developments that are leading towards digitalization in new media. The selection of first-time voter subjects from outside Ganjar's leadership area is done to avoid bias due to the influence of leadership on the subjects. This study employs a reception analysis method using in-depth interviews as primary data, which are then analyzed using the personal branding aspects theory proposed by Peter Montoya. The research identified one first-time voter who held an opposition position towards one aspect of Ganjar Pranowo's personal branding on Instagram, while the rest were in a negotiation and dominant position. The results of this research suggest that, according to first-time voters, Ganjar is viewed as an ideal leader who is close to the people, firm, easygoing with all classes of society, and respected, regardless of other intentions behind it. Ganjar uses an approach to address societal issues to gain interest and support from the public. This research is limited to posts understood by the respondents until November 2022 on the Instagram platform. It is hoped that future research will further explore this topic with broader media coverage and subjects.